2018
DOI: 10.1051/epjconf/201817009002
|View full text |Cite
|
Sign up to set email alerts
|

Detection limit of a VCO based detection chain dedicated to particles recognition and tracking

Abstract: Abstract-A particle detection chain based on CMOS-SOI VCO circuit is presented. The solution is used for the recognition and the tracking of a given particle at circuit level. TCAD simulation of the detector has been performed on a 3x3 matrix of diodes based detector for particles recognition and tracking. The current response of the detector has been used for a case study in order to determine the ability of the chain to recognize an alpha particle crossing a 3x3 detection cell. The detection limit of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The highest current, on the left, corresponds to the highest electron density and the lowest current, on the right, corresponds to the lowest charge density. These results, coming from the simulation of a 3x3 matrix presented in [19], show that the current variation can provide an information about the charge density in the detection cell.…”
Section: A Information For Trackingmentioning
confidence: 82%
See 4 more Smart Citations
“…The highest current, on the left, corresponds to the highest electron density and the lowest current, on the right, corresponds to the lowest charge density. These results, coming from the simulation of a 3x3 matrix presented in [19], show that the current variation can provide an information about the charge density in the detection cell.…”
Section: A Information For Trackingmentioning
confidence: 82%
“…In [19], it was also shown that the current shape can also give information about the distance between the charge generation and the contact. Indeed, for a contact located just above the ion, the current peak will appear earlier than for contacts located further from the generation point.…”
Section: A Information For Trackingmentioning
confidence: 99%
See 3 more Smart Citations